Comparison of the antibacterial effect of experimental primary tooth canal pastes containing octenidine dihydrochloride and calcium hydroxide: An in vitro study - Orhan, Ayşegül; Botsalı, Murat Selim; Yavşan, Zeynep Şeyda (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Octenidine dihydrochloride (OCT) has been used as a canal irrigation agent. However, no research has been done on its use as a primary root canal paste mixed with calcium hydroxide in primary teeth. Purpose: This study aims to determine the in vitro antibacterial effect of an experimental canal sealer prepared using OCT and calcium hydroxide (CaOH) on primary root canal pathogens and compare them to zinc oxide eugenol (ZOE) and iodoform paste (IP). Methods: Staphylococcus aureus (S. aureus), Streprococcus mutans (S. mutans) and Enteroccus faecalis (E. faecalis) were used as microorganisms to determine their antibacterial effect. A disc diffusion test was applied to the strains of impregnated discs with canal sealer. The number of bacteria was standardized and incubated into the Mueller–Hinton growth medium. At the end of the incubation period, the inhibition zones around the discs were measured in millimeters and recorded. Results: When the diameters of the inhibition zones were compared, the experimental canal paste obtained by mixing OCT and CaOH at a ratio of 2:1 was found to have the highest antibacterial effect against S. aureus, S. mutans and E. faecalis, and the primary tooth canal paste containing iodoform, which is used routinely in clinical practice, had the lowest antibacterial effect. Conclusion: As a result of this study, the antibacterial effect of experimental canal sealer containing OCT–CaOH on S. mutans, S. aureus and E. faecalis was found to be considerably higher than the root canal sealer containing eugenol and iodoform.